Cavernous hemangioma of mesentery involving the jejunum causing intestinal obstruction in an adult male - Srijana Thapa; Udaya Koirala; Bijendra Dhoj Joshi; Anish Baniya; Bidushi Pokhrel (Clinical Case Reports, 2022)
Abstract We present a rare case of a 45‐year‐old man with abdominal pain and features suggestive of intestinal obstruction. The CT scan of the abdomen demonstrated a large mesenteric mass involving the distal segment of jejunum. Surgical excision of the lesion and histopathological examination revealed the diagnosis of cavernous hemangioma.